2017
DOI: 10.1161/circulationaha.117.031164
|View full text |Cite
|
Sign up to set email alerts
|

International Expert Consensus on Switching Platelet P2Y 12 Receptor–Inhibiting Therapies

Abstract: Dual antiplatelet therapy with aspirin and a P2Y 12 inhibitor is the treatment of choice for the prevention of atherothrombotic events in patients with acute coronary syndromes and for those undergoing percutaneous coronary interventions. The availability of different oral P2Y 12 inhibitors (clopidogrel, prasugrel, ticagrelor) has enabled physicians to contemplate switching among therapies because of specific clinical scenarios. The recent introduction of an intravenous P2Y 12 inhibitor (cangrelor) further ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
219
1
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(245 citation statements)
references
References 97 publications
4
219
1
12
Order By: Relevance
“…Our result supported the SCOPE registry, which has shown that de‐escalation increased the rate of adverse cardiovascular events in the first month after hospital discharge . Some studies assessing the pharmacodynamic effects associated with de‐escalation to clopidogrel therapy have shown a reduction in platelet‐inhibition and an increase in the rate of high on‐treatment platelet reactivity (HPR) as compared to ticagrelor, even if 600 mg clopidogrel LD was given . These pharmacodynamic data support our findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our result supported the SCOPE registry, which has shown that de‐escalation increased the rate of adverse cardiovascular events in the first month after hospital discharge . Some studies assessing the pharmacodynamic effects associated with de‐escalation to clopidogrel therapy have shown a reduction in platelet‐inhibition and an increase in the rate of high on‐treatment platelet reactivity (HPR) as compared to ticagrelor, even if 600 mg clopidogrel LD was given . These pharmacodynamic data support our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the superior pharmacodynamic effects and clinical efficacy outcomes of ticagrelor over clopidogrel, switching between the two is common in patients with STEMI . The modalities of switching are defined as de‐escalation and escalation . In China, switching from ticagrelor to clopidogrel, which is defined as de‐escalation, after PCI is more common.…”
Section: Introductionmentioning
confidence: 99%
“…716 Based on recent results from the randomized TROPICAL-ACS (Testing responsiveness to platelet inhibition on chronic antiplatelet treatment for acute coronary syndromes) trial 717 , an approach of DAPT de-escalation guided by platelet function testing may be considered in ACS patients (NSTE-ACS and STEMI) as an alternative to 12 months potent platelet inhibition, especially for patients deemed unsuitable for maintained potent platelet inhibition. For a more detailed description of the pertinent clinical trials in the field of DAPT duration and switching antiplatelet drugs, we refer the reader to the International Expert Consensus document on Switching Platelet P2Y12 Receptor-Inhibiting Therapies 718 and the 2017 ESC Focused Update on Dual Antiplatelet Therapy in Coronary Artery Disease. 410 Following DAPT, lifelong single antiplatelet therapy (usually with aspirin) is recommended and patients should be advised not to prematurely discontinue oral antiplatelet therapy after stenting.…”
Section: Peri-interventional Treatmentmentioning
confidence: 99%
“…The pharmacodynamic effects of ticagrelor are more prompt, potent, and predictable compared with those of clopidogrel 24. It has been linked to inhibition of SMC proliferation and, hence, could be associated with reduced NIH 25.…”
Section: Discussionmentioning
confidence: 99%